2012
DOI: 10.1177/0884533612449360
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Correlation Between Circulating Levels of Citrulline and Intestinal Dysfunction in the Critically Ill?

Abstract: Low plasma citrulline levels in patients correlate well with intestinal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Surprisingly, the results show no difference between patients with renal failure and those without it. The same was observed in another study [7]. In the case of renal failure, CIT levels should be increased [8].…”
supporting
confidence: 75%
“…Surprisingly, the results show no difference between patients with renal failure and those without it. The same was observed in another study [7]. In the case of renal failure, CIT levels should be increased [8].…”
supporting
confidence: 75%
“…Several biomarkers reflecting intestinal function have been suggested recently (I-FABP, citrulline, d -lactate) [25, 26]. Future studies should establish their place in clinical practice and establish their correlations with clinical GI signs and symptoms, as well as with prognosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Piton et al detected low plasma citrulline levels in 44% of ICU patients and stated that the plasma citrulline measurement could be a sensitive marker for the functional enterocyte mass (42). Noordally et al also studied intestinal dysfunction in ICU patients and found that among several parameters (SOFA-APACHE scores, CRP, pre-albumin, albumin, citrulline, inotrophic agents, and renal dysfunction) only low plasma citrulline level correlated well with intestinal dysfunction (43). As a different perspective, Yi et al reported that exogenously administered L-citrulline exhibits gastric protection by the inhibition of neutrophil infiltration, which might be related in prevention of the increase in iNOS activity in an experimental gastric ischemia reperfusion study (44).…”
Section: Discussionmentioning
confidence: 99%
“…A plasma citrulline level below 27 µmol/L is thought to suggest intestinal pathology, and a level below 15 µmol/L is accepted as a marker of severe intestinal damage (18, 36, 39, 43). These reports suggest that the plasma citrulline level may be useful in the early detection of intestinal damage.…”
Section: Discussionmentioning
confidence: 99%